Introduction aux gender studies : manuel des études sur le genre - Bereni, Laure (De Boeck, 2008)
"Pourquoi offre-t-on des poupées aux filles et des voitures aux garçons? Pourquoi les femmes gagnent-elles moins que les hommes? Comment expliquer qu'elles effectuent les deux tiers du travail domestique? Pourquoi est-ce si mal vu pour un homme d'être efféminé? Le pouvoir est-il intrinsèquement masculin? Il s'agit là de quelques-unes des nombreuses questions auxquelles s'intéressent les études sur le genre, devenues depuis une trentaine d'années non seulement un champ de connaissances, mais aussi un outil d'analyse incontournable en sciences humaines et sociales. Au-delà de la variété des phénomènes étudiés, l'ouvrage souligne plusieurs partis pris essentiels des études sur le genre : les différences entre femmes et hommes sont le résultat d'une construction sociale et non pas le produit d'un déterminisme biologique; l'analyse ne doit pas se limiter à l'étude "d'un" sexe, mais porter sur leurs relations; le genre est un rapport de domination des hommes sur les femmes, dont les modalités et l'intensité sont sans cesse reconfigurées. Ce manuel propose un panorama clair et synthétique des notions et références essentielles des études sur le genre, en les illustrant par de nombreux exemples concrets."– Résumé de l'éditeur.
Keywords: approches et analyses; cours; discipline; discours dominant; genre; hétérosexisme; patriarcat; premier cycle; pédagogie; rapports de domination; rapports sociaux de sexe; sciences humaines; sciences sociales; sex3383; sexisme; sociologie; systèmes d'oppressions; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines